Lucrecia Martel - Gemünden, Gerd, 1959- (Contemporary film directors., 2019)
"Films like Zama and The Headless Woman have made Lucrecia Martel a fixture on festival marquees and critic's best lists. Though often allied with mainstream figures and genre frameworks, Martel works within art cinema, and since her 2001 debut The Swamp she has become one of international film's most acclaimed auteurs. Gerd Gemünden offers a career-spanning analysis of a filmmaker dedicated to revealing the ephemeral, fortuitous, and endless variety of human experience. Martel's focus on sound, touch, taste, and smell challenge film's usual emphasis on what a viewer sees. By merging of these and other experimental techniques with heightened realism, she invites audiences into film narratives at once unresolved, truncated, and elliptical. Gerd Gemünden aligns Martel's filmmaking methods with the work of other international directors who criticize--and pointedly circumvent--the high-velocity speeds of today's cinematic storytelling. He also explores how Martel's radical political critique forces viewers to rethink entitlement, race, class, and exploitation of Indigenous peoples within Argentinian society and beyond"--